(untitled) (Revista de Ciências Agroveterinárias, 2021)
The garlic crop is affected by the bacterial blight caused by Pseudomomas marginalis pv. marginalis (Pmm). Here, we evaluate the relationship between the epiphytic population fluctuation of Pmm and the severity of the disease. Cloves of the “Chonan” cultivar were inoculated with the mutant differentiating bacteria rifampicin (Pmmrf). After, they were then sown in the field. The severity was evaluated weekly over 100 random plants and the epiphytic population of Pmmrf from the leaves was serially diluted and deposited in culture medium containing rifampicin. After incubation at 28 ° C for 48 hours, Pmmrf colonies were counted. The data were submitted to Pearson’s correlation, and its significance was also evaluated. The severity of the disease and the epiphytic population started from the seventh week. The final severity reached 67 and 74% in the 2019 and 2020 cycles, respectively. However, when the epiphytic population reached 105 and 106 each year, it remained stable until the end of the culture cycle. The Pearson’s correlation achieves the 0.688 and 0.521 scores for both selected periods, indicating a moderate and significant correlation between the severity of the disease and the bacterial population.